Deteksi Dini Gangguan Gizi Melalui Pengukuran Status Gizi di Sekolah Dasar Negeri Caringin Nunggal, Ciherang - Ernawati Ernawati; Edwin Destra; Junius Kurniawan; Syilvia Cendy Enike; Anthon Eka Prayoga Khoto; Kresna Bambang Fajarivaldi; Andini Ghina Syarifah (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2024)
Nutritional status is an important determinant of overall health and well-being, having a major influence on growth, development, and overall health outcomes. The prevalence of stunting, wasting, and underweight among children in low- and middle-income countries around the world decreased by 29.1%, 6.3%, and 13.7% respectively between 2006 and 2018. For this investigation, PDCA (Plan-Do-Check-Action Method) is used. A total of 165 people participated in a community outreach initiative conducted in March 2024 at an elementary school located in West Java, Indonesia. Early detection of nutritional status is carried out by taking anthropometric measurements. Nutrition during childhood and adolescence is critical for optimal development, growth, and long-term health. Rapid assessment of nutritional status will facilitate timely interventions aimed at preventing disease and reducing premature mortality